2018
DOI: 10.1111/are.13748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofloc technology on water quality and feed utilization in the cultivation of gibel carp (Carassius auratus gibeliovar. CAS III)

Abstract: This study was designed to use sucrose as carbon source to investigate the effect of biofloc technology on water quality and feed utilization in the cultivation of gibel carp (Carassius auratus gibelio var. CAS III). Three isolipidic and isoenergetic diets were formulated containing graded levels of dietary protein (257.4, 300.7 and 353.4 g/kg). The control group (P34) was fed with 353.4 g/kg protein diet without biofloc. Three biofloc treatments (P24 + B, P29 + B and P34 + B) were fed with the three diets wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…Overall, the BFT had much higher TSS and BOD5 than the control with maximum at the last sampling point. These results agree with other work reported by Li et al (2018a) for biofloc tanks stocked with Gibel carp (Carassius auratus) that reported similar amount of TSS and BOD5 as our work, without any water exchange. The slow decline in levels of DO was probably caused by higher biological demand associated with total water biomass increment and the cumulating of biological materials and temperature range.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the BFT had much higher TSS and BOD5 than the control with maximum at the last sampling point. These results agree with other work reported by Li et al (2018a) for biofloc tanks stocked with Gibel carp (Carassius auratus) that reported similar amount of TSS and BOD5 as our work, without any water exchange. The slow decline in levels of DO was probably caused by higher biological demand associated with total water biomass increment and the cumulating of biological materials and temperature range.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, BFT is generally believed to be efficient only for the cultivation of filter‐feeding fish and shrimp species (Hargreaves, 2006) such as Macrobrachium rosenbergii (De Man) (Asaduzzaman et al, 2008), Litopenaeus vannamei (Boone) (Asaduzzaman et al, 2008; Martins et al, 2016; Xu et al, 2012) and tilapia (Avnimelech & Kochba, 2009; Crab et al, 2009; Zhang et al, 2016). Nevertheless, recent studies have shown that BFT systems can be used to culture many non‐filtering fish, such as Ictalurus punctatus (Rafinesque) (Green, 2015), Clarias gariepinus (Burchell) (Abu Bakar et al, 2015), Carassius auratus (Linnaeus) (Li et al, 2018) and Cyprinus carpio (Linnaeus) (Bakhshi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2008; Martins et al, 2016;Xu et al, 2012) and tilapia (Avnimelech & Kochba, 2009;Crab et al, 2009;Zhang et al, 2016). Nevertheless, recent studies have shown that BFT systems can be used to culture many non-filtering fish, such as Ictalurus punctatus (Rafinesque) (Green, 2015), Clarias gariepinus (Burchell) (Abu Bakar et al, 2015), Carassius auratus (Linnaeus) (Li et al, 2018) and Cyprinus carpio (Linnaeus) (Bakhshi et al, 2018).…”
mentioning
confidence: 99%
“…Bioflocs gained wide recognition because of their availability as a supplemental food source for cultured shrimp and the enhancement of conversion from inorganic nitrogen to microbial biomass with helping of heterotrophic bacteria in bioflocs (Avnimelech, 1999). Although the bioflocs' effectiveness to control inorganic nitrogen, promote growth, and enhance immunological responses has been well documented in shrimp and fish farming (Ebrahimi, Akrami, Najdegerami, Ghiasvand, & Koohsari, 2020; Kamilya et al, 2017; Li et al, 2018), the reports of bacteria screening from biofloc for nitrogen removal are still limited in aquaculture.…”
Section: Introductionmentioning
confidence: 99%